Effect of Tai Chi Exercise on Balance Function of Patients with Stroke: a Systematic Review - Shuzhen LI; Guohua ZHENG; Yucheng WANG; Shan LI; Jian HE (康复学报)
Objective:To systematically evaluate the effect of Tai Chi exercise on the balance function of patients with stroke.Methods:A literature search was performed in English and Chinese databases including Pubmed, SCI, Cochrane library, VIP, CNKI and Wan Fang, and “Tai ji” “balance” “stroke” were selected as keywords to obtain the original research articles which published before December 2014. The software of Review Manager 5.2 was applied for data analysis and quality assessment of eligible studies.Results:Seven studies with 629 participants were included. Compared with conventional rehabilitation training, Tai chi exercise and Tai chi gait training had positive effect on Berg Balance scale (BBS) index (MD=6.36, P<0.01; MD=10.20, P<0.01). Compared with routine care and movement exercises of strength, Tai Chi exercise reduced significantly the risk of fall (RR=0.30, P=0.01; RR=0.30, P=0.01).Conclusion:Tai Chi exercise can improve the balance function of patients with stroke, and its effect is superior to conventional rehabilitation training. However, more larger-scale well-designed trials are needed to confirm the superiority of Tai Chi exercise.